Phenolic profile by HPLC‐MS, biological potential, and nutritional value of a promising food: Monofloral bee pollen. Issue 5 (8th March 2018) - De‐Melo, Adriane Alexandre Machado; Estevinho, Leticia M.; Moreira, Manuela M.; Delerue‐Matos, Cristina; Freitas, Alex da Silva de; Barth, Ortrud Monika; Almeida‐Muradian, Ligia Bicudo de
Abstract: The objective of this study was to determine physicochemical and phenolic profiles as well the antioxidant and antimicrobial capacities of monofloral bee pollen samples from Brazil. Traditional methods were used. The phenolic profile was determined by high‐performance liquid chromatography‐mass spectrometry (HPLC‐MS). The protein (10.6–33.9 g/100g), lipids (3.2–8.3 g/100g), ashes (2.6–3.8 g/100g), total phenolic (5.6–29.7 mg GAE/g), and total flavonoid (0.3–19.0 mg QE/g) values were variable, even between products with the same botanical origin. The minerals analyzed were found in amounts varying between 10 mg/kg and 9.1 g/kg. Each product presented specific color parameters. Myrcia bee pollen presented the greater antioxidant capacity, and Mimosa scabrella bee pollen from Santa Catarina state was the most efficient in inhibiting bacteria and yeasts. Among the compounds identified by HPLC‐MS, flavonoid 3‐O‐glycosides predominated. The physicochemical and phenolic profiles of each sample were distinct, and there was no pattern between monofloral products of the same pollen type. Practical applications: This manuscript reports physicochemical parameters, the biological potential, and the phenolic profile from HPLC‐MS of some unknown monofloral bee pollen produced in Brazil. In addition to the possibility of the identification of phenolic compounds using a reliable technique, the current study helps to clarify one of the main questions of apicultural product researchers: Would monofloral bee pollens of the same botanical origin have similar profiles? Besides this, these results can increase consumer interest in this product and thus have positive impacts on apiculture in Brazil.